USING TECHNOLOGY DRIVEN FLIPPED CLASS TO PROMOTE ACTIVE LEARNING IN ACCOUNTING - de Oliveira Neto, José Dutra; Gomes, Gilvania de Sousa; Titton, Luiz Antônio (Revista Universo Contábil, 2017)
The flipped classroom is a pedagogical model that occurs when students become active learners and study the class content previously as homework. The new generation of students is more engaged with the intensive use of technology and increased collaborative learning. However, there are few studies about the flipped classroom method which uses technology and active methodologies resulting in better engagement and improvement in student performance. This study aims to investigate the performance gain during the class and the students’ perception of the use of the enhanced flipped classroom approach. Two accounting undergraduate classes with the same curriculum content, attending the research methodology course, had four classes using the flipped classroom approach. The sample consisted of 78 students from a public university in Brazil. Each flipped class began with a homework assignment; in addition, students should post and vote for their difficulties related to the assignment before class. In each class, there were two tests based on the most voted questions and collaborative activities between them without the help of the professor. The test results showed that in all flipped classes, there was a vast improvement after the collaborative activity being included as part of the process of knowledge construction. In addition, a survey was conducted with students and the results showed that they approve the use of enhanced flipped classroom as an appropriate teaching strategy. Universities should encourage the use of active methodologies and technological resources as a means of improving the educational processes.